Ghana : First Review Under the Extended Credit Facility Arrangement and Request for Waiver and Modifications of Performance Criteria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Ghana's First Review Under the Extended Credit Facility Arrangement and Request for Waiver and Modifications of Performance Criteria (PC). Program performance has been broadly satisfactory. All but one PC were met at end-April 2015 and structural benchmarks were largely completed, some with delays. However, there was nonobservance of the continuous PC on the ceiling on gross credit to government by Bank of Ghana in April by a small margin and the indicative targets on inflation and social protection spending were missed, the latter because of a very slight delay in some spending. The economic environment remains challenging and risks are tilted to the downside. The IMF staff recommends completion of the first review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet